1997
DOI: 10.1177/0148607197021005290
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation of High‐Amylose Cornstarch by a Mixed Population of Colonic Bacteria

Abstract: Fermentation of resistant starch by the colonic microflora was rapid and complete in 8 of 10 subjects. No adaptation of the fermentation capacity was observed after 4 weeks of dietary resistant starch supplementation. Fermentation of resistant starch increased the proportion of n-butyrate in vitro. In two subjects, fecal starch concentrations were substantially higher than in the other subjects and in vitro starch fermentation was slow and incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Other studies with RS have shown a change in SCFA and fecal pH. However, these studies administered doses ranging from 30 to 50 g/day [20][21][22] . A larger sample size and more specific fermentation metabolite analysis may be required to see a relationship between pH and SCFA concentration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies with RS have shown a change in SCFA and fecal pH. However, these studies administered doses ranging from 30 to 50 g/day [20][21][22] . A larger sample size and more specific fermentation metabolite analysis may be required to see a relationship between pH and SCFA concentration.…”
Section: Discussionmentioning
confidence: 95%
“…RS is well tolerated in humans, even in high doses (45-60 g/day) [15,20,22,23] . RS doses above 60 g/day produced greater flatulence, abdominal distension and abdominal cramping compared to control treatments in previous reports [13,24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Because each individual harbors a unique microbial community consisting of complex interactions between bacteria, pooling does pose a risk of creating interactions between bacteria that would not occur under physiological conditions. Nevertheless, pooling has been recommended [23] and utilized by a number of researchers (e.g., [19, 24 -26]) to create a general microbiota that is free of anomalous results that may arise from the microbiota from a single individual [27]. Within 2 h of collection, during which time they were kept on ice, feces were pooled and homogenized with anaerobic media (1:15 w/v) [28], and filtered through four layers of cheesecloth under continuous carbon dioxide flushing.…”
Section: In Vitro Lower Gastrointestinal Fermentationmentioning
confidence: 99%
“…26 HAS was fermented rapidly and completely during in vitro incubation with faecal slurry of both test groups, and fermentability of HAS was comparable with that of digestible starch. HAS digestibility would be affected by conditions of the experiment such as the subject of animal, starch dose and intake period.…”
Section: Discussionmentioning
confidence: 83%